PEMAKAIAN BAHASA INDONESIA TULIS OLEH SISWA WNI KETURUNAN CINA: ANALISIS KESALAHAN BERBAHASA - ., Rustam (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article is aimed to analyze written language errors made by Chinese students of private and public schools in Jambi. Data is administered by questionnaires and series of pictures taken from 200 students of senior high schools in Jambi province. The data is analyzed qualitatively. Research findings reveal that at morphological level, the most frequent errors are overgeneralization mistakes and limitation of principles comprehension of language usage. Keywords: error analysis, language usage